USE OF GRAPHIC NARRATIVES WITH PRESERVICE TEACHERS AS A MEDIATED LEARNING TOOL - Gavaldon-Hernandez, Guillermina; Gerboles-Sanchez, Ana; Adana, Francisco (PEOPLE: International Journal of Social Sciences, 2017)
Despite the use of comics in education as a tool for reading or language learning, little is known about its potential as a mediated learning tool in Higher Education settings. This paper presents a preliminary study, part of a bigger project conducted as an action-research approach which aims to gain knowledge on the use of comics in higher education as a tool to develop comprehension and thinking skills. The study was carried out at one of the Spanish universities located in the Madrid region. The study involved 71 student teachers of an undergraduate course who were trained on how to read and create comics: use of diverse types of software, composition basis, communication elements and conventions of comics’ design. Students had the freedom to create their comics choosing the software they felt most comfortable with since the purpose of the study was to analyse the composition of their stories and the way they gave meaning to learning through them. Comics were analysed and categorised according to the story they told, feelings and emotions they showed, complexity and originality. Even the comics' design was well achieved, students were focused on their graphic composition rather than on the educational problems the comics should have conveyed. Findings suggest that even though comic’s creation encouraged students’ creativity and critical reflection, developing visual thinking skills takes time and needs to be practised as it is a scaffolding process. Future studies will be focused on developing preliminary visual thinking skills before asking students to express their subject knowledge creating their graphic narratives.